A LIQUID CHROMATOGRAPHIC METHOD FOR THE RELIABLE QUANTIFICATION OF UPADACITINIB AND ITS SPECIFIED IMPURITIES - KANTHETI, SUBHASHINI; RAJU, RUDRARAJU RAMESH; GORUMUTCHU, GIRI PRASAD (International Journal of Applied Pharmaceutics, 2025)
Objective: In the proposed investigation, a novel RP-UPLC technique for the simultaneous measurement of Upadacitinib and its impurities is developed. The technique's suitability for both tablet and bulk medication dose forms was confirmed. Methods: A mobile phase consisting of 2.5 g of sodim hexane-1-sulphonic acid in 1 L of water was used to achieve an isocratic elution. The pH was adjusted to 3.0 using diluted formic acid: methanol (60:40) at a flow rate of 1 ml. min-1, using an X-Bridge Phenyl (250 x 4.6 mm, 5 µm) column. Results: Sharp peaks of Upadacitinib and its impurities were detected at 6.730, 2.823, 3.844, 4.872, 9.991, 10.499, and 10.932 min, respectively, at 256 nm as the peak using the PDA detector. Among other aspects of system suitability, USP resolution is greater than or equal to 2, USP plate count exceeds 4000, and USP tailing is good. Purity Flag "No" means that the peak is uniform (provided by Empower program). If the purity angle is smaller than the purity threshold, the peak is homogeneous. The procedure was verified in accordance with the ICH recommendations. The procedure was validated in accordance with ICH recommendations. The concentration ranges of Upadacitinib (75–450 µg/ml), impurities 1, 2, 4, and 5 (2.50–15.00 µg/ml), and impurities 3 and 6 (1.25–7.50 µg/ml) were all subjected to linear regression for the calibration curve. LOQ (34.41, 0.057, 0.211, 0.181, 0.151, 0.377, and 0.165 µg ml–1) and LOD (11.35, 0.019, 0.070, 0.060, 0.049, 0.124, and 0.055 µg ml–1) for and Upadacitinib and impurities, respectively. Accuracy, precision, and resilience were among the other confirmed characteristics that were within acceptable ranges. Conclusion: As a result, this method was chosen for shared analysis. Finally, the restrictions of the system-appropriate parameters and validation parameters are acceptable. Stability-indicating experiments under various stress conditions were successfully included to the approach.